Factors Affecting Second Language Speaking Anxiety among Entry Level Engineering Student - Nivedha, S.; Radhika, S. (International Journal of Psychosocial Rehabilitation, 2020)
In the present day language classrooms, students face difficulties to speak English. The purpose of the study is to identify the factors for the speaking anxiety among the entry level undergraduate rural engineering students. A classroom survey has been conducted and data were collected through questionnaire. The collected data were analysed using basic percentage analysis. The findings of the study showed that students not only are afraid of speaking English but to speak in their own mother tongue in front of the class. Students speak well outside the classroom. The findings show that classroom setting is also cause a speaking anxiety. The quantitative analysis of the data can be divided as: Speaking English, Speaking anxiety and classroom anxiety.